Mad honey disease: A challenging encounter in the emergency department - Sajjad Ahmed Khan; Anish Luitel; Rasmita Poudel; Bijita Aryal; Vivek K. Rauniyar; Surya Bahadur Parajuli (Clinical Case Reports)
Key Clinical Message Be aware of potential severe interactions between aged honey containing grayanotoxins and alcohol. Such combinations can exacerbate symptoms like syncope and hypotension, especially in elderly patients with pre‐existing conditions, necessitating careful evaluation and management.